Mezolitsko najdišče Pod Črmukljo pri Šembijah - Brodar, Mitja (Arheološki vestnik, 1992)
The article presents the mesolithic site of Pod Črmukljo near Šembije. There is no stratigraphy, the finds lieing in the topsoil. All the excavated deposits were sieved during the excavation, which covered only part of the site. All the artefacts are shown in the illustrations. The geometric forms, amongs which there are no segments, are indicative. The site belongs to the Tardcnoisian type of mesolithic. although it might also to the Castelnovian. However that does not mean a great internal difference on Slovenian territory.